43=3u-11

Simple and best practice solution for 43=3u-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 43=3u-11 equation:


Simplifying
43 = 3u + -11

Reorder the terms:
43 = -11 + 3u

Solving
43 = -11 + 3u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-3u' to each side of the equation.
43 + -3u = -11 + 3u + -3u

Combine like terms: 3u + -3u = 0
43 + -3u = -11 + 0
43 + -3u = -11

Add '-43' to each side of the equation.
43 + -43 + -3u = -11 + -43

Combine like terms: 43 + -43 = 0
0 + -3u = -11 + -43
-3u = -11 + -43

Combine like terms: -11 + -43 = -54
-3u = -54

Divide each side by '-3'.
u = 18

Simplifying
u = 18

See similar equations:

| x^3-12x^2-6x-12=0 | | 33b-23=b | | 29-5x=9-7x | | 12A-7=-1 | | y=0.15x+0.15 | | 7-4a=2a+2-5a | | 12=6-2y | | y-1=1/5(x-3) | | solvingx^3-12x^2-6x-12=0 | | -7-x=1+x | | -(7-7a)+4a=-23+3a | | 20x^2(-3+4x)=0 | | 1/3x-5/6x=17 | | 157=11-w | | 21x+42=-3 | | 2b^2+5b-62=0 | | 4x-11=3x+3 | | 7-g=-11 | | Y=5/2-20 | | 17j-13j=16 | | 6x+8y=480 | | 2-(6x-19)=7(x-2) | | 6x=6(x+5)+6 | | 4x-8=4x+9 | | 4=-2x+36 | | 7.4x-1.1=13.7 | | 3x^2+9x-44=0 | | 4(x+6)=21 | | 8(6)+9y=36 | | 12x-4(5+3x)=20 | | c=3+2x | | 5(2c+3d)-8d= |

Equations solver categories